UNIQUE PRESENTATION OF OSTEOPETROSIS - Dharamshi, Hasnain Abbas; Mohsin, Ali Abbas; Mustahsan, Syed Muhammad; Devi, Reshma; Iqbal, Anaam; Abidi, Syed Muhammad Ali; Ahmed, Syed Arsalan (Journal of Ayub Medical College Abbottabad, 2016)
Osteopetrosis is a rare hereditary disorder of osteoclast dysfunction leading to abnormally dense and sclerotic bones that are fragile and break easily. It can be inherited in various patterns like autosomal-dominant, autosomal-recessive or as X-linked traits, but the most grievous forms of its inheritance are the autosomal-recessive ones, which show early onset and are associated with very poor prognosis. We report here the case of an asymptomatic young boy, who was diagnosed as the case of autosomal recessive osteopetrosis on the basis of his genetic studies. The reason for his unusual asymptomatic disease was the location of mutation in TCIRG1 gene that was revealed from his genetic studies. Another unusual point about him was his survival at this age, which is surprisingly rewarding as patients with autosomal recessive osteopetrosis usually die earlier by the age of 2-3 years.